Development of Interactive Learning Media on Temperature and Heat Materials Using the ADDIE Method: Pengembangan Media Pembelajaran Interaktif Pada Materi Suhu dan Kalor Menggunakan Metode ADDIE - Mega Ananda Putri; A. Bahri Joni; Meiyi Darlies (Jurnal Teknologi Informatika Multimedia Digital, 2025)
The use of technology in education is very important for enhancing student engagement in the learning process. This research aims to develop interactive learning media based on educational games on the topic of temperature and heat for fifth-grade elementary school students. The method used is ADDIE, which includes five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, the needs of students and teachers who are still using conventional methods were identified. After development, the learning media was validated by content and media experts with percentages of 90% and 96%, indicating the feasibility of using this media. Class trials showed an improvement in student understanding, with an average pretest score of 60 and a posttest score of 83.8, along with an N-Gain of 0.63 indicating a moderate increase. The results of this study indicate that interactive learning media can improve student learning outcomes and provide recommendations for further development, including the addition of audio features to enhance the audio-visual aspects of learning.